Inflamación crónica granulomatosa en el pez teleósteo Piaractus mesopotamicus: Modelo de estudio histopatológico - Manrique, Wilson G. [UNESP]; Figueiredo, Mayra A.P.; Belo, Marco A.A. [UNESP]; Martins, Maurício L.; Moraes, Flávio R. [UNESP] (Universidad de Cordoba, 2017)
Objective. This study evaluated the cell kinetic and formation of granuloma during chronic inflammation induced by Bacillus Calmette-Guérin (BCG) in the skeletal muscle of Piaractus mesopotamicus, as a histopathology model to study innate immunity. Materials and methods. Sixty fish were divided in two groups: BCG-inoculated and non-inoculated fish and the inflammatory response analyzed 3, 7, 14, 21 and 33 days post-inoculation (DPI) by histopathology after hematoxylin-eosin and Ziehl-Neelsen staining. Results. 3 DPI of BCG showed a diffuse inflammatory reaction mostly composed by mononuclear cells. The inflammation continued diffuse 7 DPI initiating the cellular organization surrounding the inoculum and have continued at 14 DPI with discrete presence of epithelioid-like type cells with acidophilic cytoplasm and floppy chromatin. Higher cellular organization (21 DPI) surrounding the granuloma with intense peripheral mononuclear inflammatory infiltrate and nevertheless, an increase in the number of fibroblasts and macrophage-like cells was observed. The inflammatory process became less diffuse 33 DPI with formation of small amount of granuloma surrounded by the same type of reaction found in bigger granuloma. Both the young and old granuloma presented typical characteristic around the inoculum composed by a layer of epithelioid-like type cells, besides macrophages, some lymphocytes and abundant fibroblasts. Conclusions. This study showed the feasibility in the use of pacus to study chronic granulomatous inflammatory response induced by BCG, characterized by changes in the kinetics of inflammatory cells in skeletal muscle classifying as immune-epithelioid type, similar to granulomatous inflammation caused by M. marinum in teleost fish.
Chronic granulomatous inflammation in teleost fish Piaractus mesopotamicus: Histopathology model study
Keywords: BCG; Granuloma; Macrophage; Mycobacterium; Pacu (Source: CAB)